Promoting Continuous Quality Improvement in Online Education: The Meta Model - Holly McCracken; Eileen Dittmar (Online Learning, 2012)
Experienced e-learning faculty members share strategies for implementing a comprehensive faculty development program essential to continuous improvement of instructional skills. The high-impact META Model (centered around Mentoring, Engagement, Technology, and Assessment) promotes information sharing and content creation, and fosters collaboration among a large geographically dispersed postsecondary faculty teaching one hundred percent online. Among its goals are to increase student satisfaction, promote instructional quality and continuous improvement, and motivate faculty. Model components include customized individual mentoring, an emphasis on continuous professional engagement and development, the integration of technologies to reinforce ongoing communication and interaction, and ongoing assessment measures using self, peer, and student evaluations to guide the development of exemplary practices.